2015
DOI: 10.1002/adma.201502037
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects Between Phosphonium‐Alkylphosphate Ionic Liquids and Zinc Dialkyldithiophosphate (ZDDP) as Lubricant Additives

Abstract: Unique synergistic effects between phosphonium-alkylphosphate ionic liquids (ILs) and zinc dialkyldithiophosphate (ZDDP) are discovered when used together as lubricant additives, resulting in significant friction and wear reduction along with distinct tribofilm composition and mechanical properties. The synergism is attributed to the remarkably 30-70× higher-than-nominal concentrations of hypothetical new compounds (via anion exchange between IL and ZDDP) on the fluid surface/interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
142
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 185 publications
(149 citation statements)
references
References 35 publications
6
142
1
Order By: Relevance
“…An emerging alternative to ZDDP is oil-miscible ionic liquids (ILs). Recent efforts by Qu et al have developed a group of fully oil-miscible phosphonium-phosphate ILs as next-generation anti-wear additives [12][13][14][15][16]. In addition to excellent oil-miscibility, these ILs also demonstrate a number of other features, such as high thermal stability, non-corrosiveness, excellent wettability on metal The aforementioned information clearly reflects that pronounced progress has been made towards developing highly efficient ILs for engine applications.…”
Section: Introductionmentioning
confidence: 99%
“…An emerging alternative to ZDDP is oil-miscible ionic liquids (ILs). Recent efforts by Qu et al have developed a group of fully oil-miscible phosphonium-phosphate ILs as next-generation anti-wear additives [12][13][14][15][16]. In addition to excellent oil-miscibility, these ILs also demonstrate a number of other features, such as high thermal stability, non-corrosiveness, excellent wettability on metal The aforementioned information clearly reflects that pronounced progress has been made towards developing highly efficient ILs for engine applications.…”
Section: Introductionmentioning
confidence: 99%
“…The above results indicate that N 88816 S P and P 888S S P can remarkably enhance the EP and lubricating behavior of ZDDP. Moreover, it has been established that this phenomenon can be attributed to the synergistic effects between ILs and ZDDP [39]. Therefore, it is feasible for the two ILs to partly or completely replace ZDDP for practical use, and this is highly likely to decrease the toxicity caused by zinc to the catalyst system.…”
mentioning
confidence: 99%
“…Compared to commercial lubricating oils of similar viscosities, this IL shows significantly improved friction coefficient and thermal stability. Studies from our group and others have shown that [P6, 6,6,14] + cation based ILs are potential additives for hydrocarbon base oils for a variety of surfaces [19][20][21][22][23][24][25][26][27]. As little as 2 mol% IL dissolved in a base oil lubricates as effectively as the pure IL, and low concentration IL-oil mixtures are much more effective lubricants than the pure base oil [20][21][22], or oils with traditional additives [22,28].…”
Section: Introductionmentioning
confidence: 99%